2016
DOI: 10.1108/mi.2016.6510
|View full text |Cite
|
Sign up to set email alerts
|

Tennis enhances well-being in university students

Abstract: Sports and physical activity are widely recommended, both as guidelines and in clinical practice, because of their broad range of positive effects on health, depression, anxiety, and psychological well-being. While several studies have examined the anti-depressive and anxiolytic effects of physical activity in clinical populations, and fewer studies have focused on the nonclinical populations, the relationship between tennis and well-being has not been clearly investigated. This study was carried out with 76 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Concerning tennis, to our knowledge there are no published studies that investigate the acute psychological effects of a single session; and the relevant literature regarding this type of exercise is quite limited. There is actually only one published study in which the impact of a 13-week tennis programme on mental health was investigated; it revealed positive results regarding stress and depression, especially in young athletes (Yazici et al, 2016). Nevertheless, in the present study, tennis presented the poorest results compared to gymnastics and GTD.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Concerning tennis, to our knowledge there are no published studies that investigate the acute psychological effects of a single session; and the relevant literature regarding this type of exercise is quite limited. There is actually only one published study in which the impact of a 13-week tennis programme on mental health was investigated; it revealed positive results regarding stress and depression, especially in young athletes (Yazici et al, 2016). Nevertheless, in the present study, tennis presented the poorest results compared to gymnastics and GTD.…”
Section: Discussioncontrasting
confidence: 58%
“…In a recent large-scale study (Chekroud et al, 2018), it was found that people who physically exercise, have approximately 43% fewer days/per month of poor mental health than those who do not exercise. Moreover, sufficient research evidence supports the value of several types of leisure-time PA and physical exercise, such as popular team sports (Chekroud et al, 2018), tennis (Groppel & DiNubile, 2009;Yazici, Gul, Yazici, & Gul, 2016), dance (e.g., ballroom dance [Haboush, Floyd, Caron, LaSota, & Alvarez, 2006], Greek traditional dance [Mavrovouniotis, Argyriadou, & Papaioannou, 2010]), aerobic exercise (Broman-Fulks, Berman, Rabian, & Webster, 2004;McAuley et al, 2000), and mindful exercise (Hofmann, Sawyer, Witt, & Oh, 2010) for positive psychological outcomes. It is interesting to note that several researchers report that even one single session of leisure-time PA/ physical exercise, such as aerobic gymnastics (Genti, Goulimaris, & Yfantidou, 2009;Lox & Rudolph, 1994;Netz & Lidor, 2003;Panagopoulou, Charalampopoulos, Piperidou, & Rokka, 2016;Rokka, Mavridis, & Kouli, 2010), Greek traditional dance (GTD) (Genti et al, 2009), or mindful exercise (Netz & Lidor, 2003) can trigger positive psychological responses.…”
Section: Introductionmentioning
confidence: 99%
“…In the classroom, clear assessment criteria, classroom policies, and project deadlines can eliminate student frustration, dissatisfaction, and withdrawal from active learning (Mokgele and Rothman, 2014). Sports and physical activity have also been shown to decrease depression and stress and increase student well-being (Yazici et al, 2016). Campus libraries contribute to promoting student well-being by ensuring easy access to learning resources and a learning space for all students (Cox and Brewster, 2020).…”
Section: Student Well-beingmentioning
confidence: 99%
“…Student well-being includes concepts of motivation, identity, self-esteem, self-efficacy, and self-regulation in the context of learning and matriculating through the program to get a degree (Willis et al, 2019). Student well-being has shown to increase their engagement in learning activities, meaning making, a sense of belonging, positive relationships with others, autonomy, and competencies (Sortheix and Lönnqvist, 2015;Baik et al, 2016;Cox and Brewster, 2020) and reduce their burn-out, stress, frustration, dissatisfaction, and withdrawal from active learning (Flinchbaugh et al, 2012;Mokgele and Rothman, 2014;Yazici et al, 2016). Therefore, well-being not only fosters student academic achievement, but also prepares students for lifelong success (Mahatmya et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Wellbeing measures have included various World Health Organization (WHO) measures (Helou et al, 2019;Philippe et al, 2019), the Warwick and Edinburgh Mental Wellbeing Scale (WEMWBS; Harding et al, 2019;Kidger et al, 2019), the Positive emotion, Engagement, Relationship, Meaning and Accomplishment (PERMA) profiler (Ascenso et al, 2017;Smith et al, 2020), the Satisfaction with Life scale (Samaranayake and Fernando, 2011;Moate et al, 2019) and various versions of Ryff 's Psychological Wellbeing Scale (PWB;Chraif and Dumitru, 2015;De Clercq et al, 2019). Unidimensional mental health measures have included the Beck depression and anxiety inventories (Yazici et al, 2016;Yüksel and Bahadir-Yilmaz, 2019), the Depression Anxiety Stress scale (Koops and Kuebel, 2019), and the Kessler scale of psychological distress (K10; Brewer et al, 2019). Multidimensional measures used were, for example, the General Health Questionnaire (Bore et al, 2016), the Personal Health Questionnaire (PHQ 9; Lipson et al, 2016), and the SF12 (Wilks et al, 2020).…”
Section: Introductionmentioning
confidence: 99%